FREQUENCY OF NEWLY DIAGNOSED DIABETES MELLITUS IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - Hayat, Umar; Khan, Mattiullah; Kazmi, Nasir Hussain Shah; Ali, Nasir; nawaz, Rab; Mufti, Waqar A; Khan, Faisal Iftikhar; Khan, Airaz (Journal of Ayub Medical College Abbottabad, 2014)
Background: Diabetes is a major cause of heart disease. Death rate for heart disease is about 2-4 times higher among adults with diabetes then among those without diabetes. In setting of acute Myocardial infarction hyperglycemia is associated with adverse out come even after numerous cardiac variable linked to the outcome are adjusted. Elevated plasma glucose at admission is predictor of long term and in hospital outcome in patients with acute Myocardial infarction. After acute myocardial infarction high admission blood glucose level are common with increased risk of death in subjects with or without diabetes. The objective of study was to determine the frequency of newly diagnosis diabetes presenting with acute myocardial infarction. Methods: This cross sectional study was conducted in department of Cardiology, Ayub Teaching Hospital from June to November 2014. All patients admitted to coronary care unit with acute myocardial infarction and who were not known diabetics were enrolled by consecutive non probability sampling. Patients of either gender were included Hospital. Descriptive statistics were used to determine the frequency of newly diagnosed diabetics. RESULT: Out of 91 enrolled patients in our study, 60 (65.9%) were male, 31 (34.1%) were female. 27 (29.6%) patients were newly diagnosed diabetics. CONCLUSION: The frequency of newly diagnosed diabetics is quite high in patients with acute myocardial infarction. Hence all patients were not known diabetics and present with acute myocardial infarction should be screened for new onset of diabetes. Keywords: Newly diagnosed diabetes, Acute Myocardial infarction, diabetes mellitus